Strengthening vocational teacher education in Jamaica: An example of incremental, institution development - McClelland, Jerry
A small-scale, short-term institution strengthening project between the College of Arts, Science and Technology (CAST) in Jamaica and the University of Minnesota College of Home Economics focused on the improvement of vocational teacher education in Jamaica. CAST's technical teacher education programme prepares teachers in the areas of business studies, secretarial studies, home economics, construction technology, electrical technology, and mechanical technology. A partnership between CAST and the University of Minnesota provided CAST with technical assistance in the home economics area and opportunities for educators from both institutions to study at the other's programme. Personnel involved in the partnership have been given opportunities to develop curriculum and teaching materials for cultures different from their own, improve services to international students at their own institution, and develop research projects
Keywords: College of Arts, Science and Technology